Spatial familiness: a bridge between family business and economic geography - Rodrigo Basco; Lech Suwala (A research agenda for family business. A way ahead for the field, 2020)
There is both a practical and a scholarly need for the thorough examination of the nexus between family firms and economic spaces (e.g. locations, places, landscapes). The authors address this nexus through two approaches. First, they explore economic spaces' effect on family firms by considering the influence different types of economic spaces have on firm behavior and firm performance. Second, they explore family firms' effect on economic spaces by attempting to clarify the role family firms play in different economic spaces. The explores the peculiarities of family firms and their recursive relationships with economic spaces. The authors propose a journey that includes three avenues—macro-, meso-, and micro-foundations—to organize current debates on and to further our understanding of spatial familiness.
Keywords: R50; R11; R12; R58; R2; O18; 330; Family Firms; Regional Development; Regional Economics; Economic Geography; Regional Studies; Regional Science; Family Business Studies